Does Lean Improve Labor Standards? Management and Social Performance in the Nike Supply Chain - Distelhorst, Greg; Hainmueller, Jens; Locke, Richard M. (Management Science, 2017)
This study tests the hypothesis that lean manufacturing improves the social performance of manufacturers in emerging markets. We analyze an intervention by Nike, Inc., to promote the adoption of lean manufacturing in its apparel supply chain across 11 developing countries. Using difference-in-differences estimates from a panel of more than 300 factories, we find that lean adoption was associated with a 15 percentage point reduction in noncompliance with labor standards that primarily reflect factory wage and work hour practices. However, we find a null effect on factory health and safety standards. This pattern is consistent with a causal mechanism that links lean to improved social performance through changes in labor relations, rather than improved management systems. These findings offer evidence that capability-building interventions may reduce social harm in global supply chains. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2369 . This paper was accepted by Bruno Cassiman, business strategy.